Effect of Different Diets on Lifetime of Brown-banded Cockroaches, Supella longipalpa (Blattodea: Blattellidae) - Hadis Mosayebian; Hamid Reza Basseri; Mojgan Baniardalani; Yavar Rassi; Hossein Ladonni (Tehran University of Medical Sciences, 2017)
Background: The brown-banded cockroach, Supella longipalpa, is not as common as the German cockroach in Iran. This species seeks out areas that are very warm most of the time, and prefer warmer area than what German cockroaches prefer. There is relationship between development of instars and diet of cockroaches. The aim of this study was to determine the effect of different diets on biology, life cycle on nymphal stages of S. longipalpa in laboratory condition prior to investigate the insecticide resistance status of this species in residence area in Iran. Methods: The cockroaches were reared in the insectary of School of Public Health, Tehran University of Medical Sciences, condition and the population divided in four equal groups. The effect of four different diets on life cycle of S. longipalpa was studied to determine the effect of them on the lifetime of each nymphal stage. Results: The diets significantly affected on growth and development of immature life stages of S. longipalpa. Based on introduced diets to the cockroache populations, total immature life cycle was 54, 58, 60 and 66 d for diets 2,4,1, and 3 relatively. However, the overall lifetime of S. longipalpa in average was about 225 days. Conclusion: As far as urban pest control is concerned, the result of this study will facilitate any operational programs for control of S. longipalpa. Among the different tested diets, diets 2 and 4 with less duration would be recommended for rearing of S. longipalpa in laboratory condition.